DIAGNOSIS KESULITAN BELAJAR DALAM MEWUJUDKAN EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Andri Sukrinaldi; Muslim Afandi; Mhd. Subhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning Difficulty Diagnosis is a crucial instrument in the psychology of Islamic Religious Education learning to identify students' cognitive, affective, and psychomotor barriers. This study aims to analyze the basic concepts, technical procedures, and follow-up strategies of LDD in the context of religious learning. Using a qualitative literature study method, the results show that the effectiveness of LDD depends on the sharpness of symptom identification, localization of barriers, and accuracy of prognosis. Factors causing learning difficulties include internal aspects such as low motivation and cognitive disorders, as well as external factors such as the social environment and conventional teaching methods. As a follow-up, the implementation of remedial teaching integrated with an educational psychology approach is proven to be able to restore academic performance and holistic spiritual character development of students.